2014
DOI: 10.1007/s11604-013-0272-y
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficient is a prognostic factor of head and neck squamous cell carcinoma treated with radiotherapy

Abstract: ADC is an independent predictor of prognosis in HNSCC treated with radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Pretreatment tumor ADC values have been shown to be predictors of treatment response in head and neck cancers. Previous head and neck squamous cell carcinoma studies have found significantly higher tumor ADC values in patients with LF, [5][6][7]10 nodal failure, 4 or poor treatment response, [8][9] while other studies have shown a similar trend in the ADC values that did not reach statistical significance. [17][18][19] It has been postulated that poor outcomes of some squamous cell carcinomas are due to tumor factors that are known to increase ADC values, such as micronecrosis, lower cellularity, and, more recently, negative human papillomavirus status and high stromal content.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Pretreatment tumor ADC values have been shown to be predictors of treatment response in head and neck cancers. Previous head and neck squamous cell carcinoma studies have found significantly higher tumor ADC values in patients with LF, [5][6][7]10 nodal failure, 4 or poor treatment response, [8][9] while other studies have shown a similar trend in the ADC values that did not reach statistical significance. [17][18][19] It has been postulated that poor outcomes of some squamous cell carcinomas are due to tumor factors that are known to increase ADC values, such as micronecrosis, lower cellularity, and, more recently, negative human papillomavirus status and high stromal content.…”
Section: Discussionmentioning
confidence: 92%
“…It has been shown subsequently that more advanced nonGaussian models for ADC analysis influence the ADC in NPC. 41 In head and neck squamous cell carcinoma, the choice of b-values may also influence the accuracy of ADC for the prediction of treatment response, and some authors have proposed using ADCs calculated from the mid/high b-range (300/500-1000 s/mm 2 ) 9,10 to predict locoregional response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Merging evidence suggests that diffusion-weighted magnetic resonance imaging (DWI-MRI) improves tissue characterization, staging, and response to treatment in HNSSC. 610 Conventional diffusion-weighted imaging (DWI), with a mono-exponential model, could not separate perfusion and true diffusion-related effect. This could be resolved in intra-voxel incoherent motion (IVIM) with a bi-exponential model.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in recent years, DWI has been considered a good candidate as a noninvasive biomarker for predicting and monitoring treatment responses. Consequently, many studies have assessed DWI parameters (ADC values) with tumor response to chemoradiation therapy, [16][17][18][19][20][21][22][23][24] 2 ) has been applied successfully to HNSCC for tumor grading and work-up for recurrence following treatment. [25][26][27] In addition, a histogram-based approach with ADC maps has been used in neuro-oncologic imaging to differentiate tumor progression from pseudoprogession and to evaluate tumor grades and even gene mutations.…”
Section: Introductionmentioning
confidence: 99%